Assessing Students' Religious Proficiency Using Glock-Stark Dimensions and Its Impact on Curriculum Development and Islamic Education Learning - Juanda, Anda; Nurhayati, Tati; Mahdi, Mahdi; Nasrudin, Dindin; Muhtar, Siti Nuraeni (PAEDAGOGIA, 2024)
This study intends to analyze the religiosity of high school students using the Glock-Stark theory and its impact on curriculum development and Islamic Education learning. The research utilized a mixed-method approach with a sequential explanatory design. The data show that the level of religiosity among students differs. The ANOVA test indicates that there are substantial differences in religiosity levels across 9 high schools in West Java. Research shows that variations in students' levels of religiosity are shaped by internal factors like cognitive abilities and external factors like the religious environment of families, schools, and communities, including the characteristics of teachers. The novelty of this study lies in its comprehensive examination of both internal and external factors influencing religiosity and its specific focus on the implications for curriculum development in Islamic Education. This study's findings have significant implications for curriculum development and school physical activity instruction, encompassing planning, execution, and learning assessment